Antibacterial and Anti-Inflammatory Coating Materials for Orthopedic Implants: A Review - Gang Tan (MDPI AG, 2021)
Orthopedic implant failure is the most common complication of orthopedic surgery, causing serious trauma and resulting in a tremendous economic burden for patients. There are many reasons for implant failure, among which peri-implant infection (or implant-related infection) and aseptic loosening are the most important. At present, orthopedic doctors have many methods to treat these complications, such as revision surgery, which have shown good results. However, if peri-implant infection can be prevented, this will bring about significant social benefits. Many studies have focused on adding antibacterial substances to the implant coating, and with a deeper understanding of the mechanism of implant failure, adding such substances by different modification methods has become a research hot spot. This review aims to summarize the antibacterial and anti-inflammatory substances that can be used as coating materials in orthopedic implants and to provide a reference for the prevention and treatment of implant failure caused by implant-related infection and excessive inflammation.